Plastic extraction from dryer lint (PEDL): a low-tech, mass-based approach to quantify plastic microfibers in complex dryer lint - James Farnan; MC Cicenia; Troy Langknecht; Sarah M. Davis; Dounia Elkhatib; Robert M. Burgess; Kay T. Ho (Environmental Science and Pollution Research, 2026)

Tracing Blue Carbon Flows Across Diverse Seascapes - Christopher J. Fulton; Diego R. Barneche; Kay Davis; Cal Faubel; Cecilia Pascelli; Julie Vercelloni; Shaun K. Wilson (Global Change Biology, 2025)
Plants occupying coastal ecosystems draw in carbon dioxide (CO 2 ) from the air and water around them during photosynthesis. A fraction of this CO 2 becomes fixed into plant biomass and can eventually contribute to the blue carbon pool—organic carbon (C org ) sequestered in slow‐turnover sinks. An important step in protecting and enhancing this natural carbon sequestration pathway is determining the relative contributions of different coastal plants to this blue carbon pool in durable sinks. We compiled a global dataset of coastal soil carbon measurements and used a Bayesian hierarchical meta‐regression model to explore the relative contribution of local (autochthonous) versus external (allochthonous) sources of C org in the soils beneath tidal saltmarsh, mangrove, and seagrass wetlands. We found most soil C org in coastal wetlands came from allochthonous sources, rather than the habitat‐forming plants. Managing climate‐resilient blue carbon seascapes, therefore, requires an awareness of this portfolio of contributors to soil carbon sequestration. However, study design aspects such as soil sampling depth, levels of sample replication, and the modeling approach used to trace C org can have pronounced effects on the estimated contributions of different carbon sources. We outline a roadmap for improving how we track the various drivers of soil carbon sequestration in diverse mosaics of coastal vegetation.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Contrasting Radium-Derived Groundwater Exchange and Nutrient Lateral Fluxes in a Natural Mangrove Versus an Artificial Canal - Praktan D. Wadnerkar; Bayartungalag Batsaikhan; Stephen R. Conrad; Kay Davis; Rogger E. Correa; Ceylena Holloway; Shane A. White; Christian J. Sanders; Isaac R. Santos (Estuaries and Coasts, 2021)

Fifty Years of Sporadic Coral Reef Calcification Estimates at One Tree Island, Great Barrier Reef: Is it Enough to Imply Long Term Trends? - Kay L. Davis; Ashly McMahon; Brendan Kelaher; Emily Shaw; Isaac R Santos (Frontiers in Marine Science, 2019)

Spatial and temporal expression of the Cre gene under the control of the MMTV-LTR in different lines of transgenic mice - Kay-Uwe Wagner; Toni Ward; Barbara Davis; Roger Wiseman; Lothar Hennighausen (Transgenic Research, 2001)